2012
DOI: 10.5009/gnl.2012.6.3.339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Oral Administration of Mosapride Citrate on Capsule Endoscopy Completion Rate

Abstract: Background/AimsIn capsule endoscopy (CE), the capsule does not always reach the cecum within its battery life, which may reduce its diagnostic yield. We evaluated the effect of mosapride citrate, a 5-hydroxytryptamine-4 agonist that increases gastrointestinal motility, on CE completion.MethodsIn a retrospective study, we performed univariate and multivariate analyses for 232 CE procedures performed at our hospital. To identify factors that affect CE completion, the following data were systematically collected:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The current and previous study protocols are shown in Tables and previous data suggested that prokinetic drugs reduce the gastric transit and small bowel transit times, leading to an improvement of the completion rate . Therefore, two prokinetic drugs, mosapride citrate and metoclopramide were used in the current protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The current and previous study protocols are shown in Tables and previous data suggested that prokinetic drugs reduce the gastric transit and small bowel transit times, leading to an improvement of the completion rate . Therefore, two prokinetic drugs, mosapride citrate and metoclopramide were used in the current protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Mosapride citrate (mosapride), a selective 5‐hydroxytryptamine‐4 receptor agonist, increases gastrointestinal motility . Our recent data suggest that oral administration of mosapride reduces the gastric transit time and small bowel transit time during small bowel capsule procedures. A few clinical studies have shown that mosapride in combination with polyethylene glycol solution (PEG) may enhance bowel cleansing and improve acceptability and tolerability for patients .…”
Section: Methodsmentioning
confidence: 99%
“…Mosapride is an emerging prokinetic agent, working as a 5-hydroxytryptamine receptor 4 agonist and accelerating both gastric emptying and peristalsis of the small intestine (28). Wei et al (29) and Ida et al (30) recommended that patients received 10 mg mosapride citrate 30-60 min prior to capsule ingestion. However, the dosage and administration time of mosapride remain to be evaluated.…”
Section: Discussionmentioning
confidence: 99%